Implementation of Language Games Through Pictured Letter Cards in an Effort to Improve The Beginning Reading Skills of Grade I Students at State Elementary School UPT 060837 - Susanti, Dewi; Sutikno; Kartolo, Rahmat; Afrida Harahap, Dedek; Sibarani, Asni (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to describe the implementation of a picture card-based language game in improving the early reading skills of first-grade students at the UPT SD Negeri 060837, Medan Barat District. This study also identifies the obstacles faced and the solutions implemented during the learning process. This type of research uses a qualitative field research approach. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used are data reduction, data display/presentation, and conclusions/verification. The research method used is classroom action research (CAR) which consists of two cycles with stages of planning, implementation, observation, and reflection. The research subjects are first-grade students, with data collected through observation, interviews, and documentation. The results of the study showed that the use of language games using picture letter cards significantly improved students' motivation and early reading skills. Students' activeness and enthusiasm increased, as evidenced by their improved ability to recognize letters, syllables, and words. Challenges identified included limited media, teachers' lack of experience in using this method, and students' low self-confidence. Solutions implemented included teacher training, increased creativity in media use, and support for a conducive learning environment. In conclusion, the application of language games through the media of picture letter cards is an effective method to improve the early reading skills of first grade students. With the right approach, this game not only improves reading skills, but also creates a fun and interactive learning atmosphere